A laboratory preparation of waste incineration fly ash-based silicon calcium plate and a preparation method thereof

CN121929989BActive Publication Date: 2026-10-23CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610134392.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-30
Publication Date
2026-10-23
Estimated Expiration
2046-01-30

AI Technical Summary

Technical Problem

[0005]综上,现有垃圾焚烧飞灰存在堆积污染与资源化需求迫切的双重问题,而硅酸钙板生产面临原材料替代的现实需求

Benefits of technology

本发明提供的一种实验室制备垃圾焚烧飞灰基硅钙板及其制备方法,通过以垃圾焚烧飞灰为主要钙源,搭配多种原料并采用特定制备工艺,实现了危险固体废物的资源化利用,减少了天然矿物资源的消耗和危险废物的堆积量,降低了环境风险。从背景技术可知,垃圾焚烧飞灰是危险固体废物,现有的处理方式无法平衡产出量,长期堆积填埋有有毒物质渗漏风险,容易引发化学污染事件,对环境产生不可逆的影响,本发明通过优化原材料组成,使固体废物在原材料灰分的组成中达到80%,同时垃圾焚烧飞灰的掺入量超过50%,显著的解决了垃圾焚烧飞灰堆积过多无法资源化的问题,同时以固废替代传统生产过程中的天然原料,极大程度减少了自然资源的消耗,兼具环保和经济效益;并且通过优化原料配比,特别是引入了特定含量的纸浆纤维与硅酸钠,利用纤维引导水热合成产物定向生长,形成了增强增韧的纤维-晶相-凝胶相三元网状结构,大幅提升了板材的综合性能;同时,实验室微缩制备方法可模拟工业生产全流程,为后续大规模工业化生产提供可靠的预实验数据指导,兼具环境效益、经济效益和实用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121929989B_ABST
    Figure CN121929989B_ABST
Patent Text Reader

Abstract

The application provides a laboratory-prepared garbage incineration fly ash-based silicon-calcium plate and a preparation method thereof, the silicon-calcium plate comprises cement 20-25 parts by mass, fly ash 10-15 parts by mass, desulfurization gypsum 3-5 parts by mass, silica ash 3-5 parts by mass, fly ash 50-80 parts by mass, quartz sand 80-100 parts by mass, sodium silicate 10-15 parts by mass, paper pulp fiber 5-8 parts by mass and water 54-60 parts by mass. The preparation method comprises the following steps: mixing the fiber, the sodium silicate and the water to prepare pulp; mixing other solid raw materials to prepare powder; mixing the pulp and the powder to form a pressing material; pressing the pressing material into a plate blank through a mold; and then performing autoclaved curing and drying. The application takes garbage incineration fly ash as a main calcium source, realizes the resource utilization of hazardous waste through a specific formula and process, and the prepared plate has the advantages of light weight, high strength and effective solidification of heavy metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to a laboratory preparation method for a calcium silicate board based on waste incineration fly ash. Background Technology

[0002] With the shift in my country's municipal solid waste treatment methods from landfill to incineration, a large amount of fly ash from waste incineration is generated as hazardous solid waste. This fly ash mainly consists of calcium oxide and some chloride salts, and also contains large amounts of heavy metals and organic toxins such as dioxins. Even after detoxification and fixation, the byproducts generated by current mainstream treatment methods still require landfill disposal, resulting in a significant waste of land resources and potential environmental risks. Therefore, the resource utilization of waste incineration fly ash has become an urgent problem to be solved.

[0003] Calcium silicate board, as a green building material, features low density, high strength, and excellent fire resistance. It is primarily produced by the hydration reaction of silicon-rich and calcium-rich materials under high-temperature conditions, with tobermorite as the core phase. Tobermorite possesses a high specific surface area and strong ion exchange capacity, exhibiting excellent adsorption effects for heavy metal ions such as cobalt, copper, cadmium, chromium, and lead, showing broad application prospects in the treatment of silicon- and calcium-rich solid waste containing heavy metals. However, traditional calcium silicate board production mainly uses limestone and quartz sand as raw materials, with the addition of fibers for auxiliary preparation. This process inevitably consumes natural mineral resources, thus necessitating the search for new alternative raw materials to achieve sustainable production. Utilizing fly ash from waste incineration as a calcium source for calcium silicate board production can achieve both the harmless treatment of hazardous solid waste and meet the raw material requirements for calcium silicate board production, achieving the dual goals of solid waste treatment and green building material production.

[0004] Currently, the technology for the resource utilization of waste incineration fly ash is still immature. Mainstream alkali-activated resource utilization methods are limited by reaction characteristics, resulting in brittle building materials and severely restricting their application. However, the high-temperature, high-pressure environment during the production of calcium silicate boards provides suitable conditions for the hydrothermal treatment of waste incineration fly ash, while also fully utilizing the abundant calcium components in the fly ash, reducing dependence on natural mineral resources.

[0005] In summary, existing methods for producing calcium silicate board from waste incineration fly ash present the dual challenges of pollution from accumulation and the urgent need for resource utilization. Meanwhile, the production of calcium silicate board faces a real need for raw material substitution. To reduce production energy consumption, control costs, and improve economic efficiency, developing a technology for preparing calcium silicate board from waste incineration fly ash has become an important research direction in the fields of building materials and solid waste treatment. Summary of the Invention

[0006] In view of this, the purpose of this invention is to provide a laboratory preparation method for a calcium silicate board based on waste incineration fly ash. By adding pulp fiber and sodium silicate in a specific ratio and combining it with a step-by-step molding process, the efficient resource utilization of waste incineration fly ash is successfully achieved, while a lightweight calcium silicate board with excellent mechanical properties and environmental benefits is prepared.

[0007] The technical solution adopted by this invention to solve its technical problem is: A laboratory-prepared waste incineration fly ash-based calcium silicate board is provided, comprising: 20-25 parts cement, 10-15 parts fly ash, 3-5 parts desulfurized gypsum, 3-5 parts silica fume, 50-80 parts fly ash, 80-100 parts quartz sand, 10-15 parts sodium silicate, 5-8 parts pulp fiber, and 54-60 parts water.

[0008] Preferably, the average particle size D50 of the cement is 13~16μm; the average particle size D50 of the fly ash is 22~26μm; the average particle size D50 of the silica fume is 8~10μm; the average particle size D50 of the desulfurized gypsum is 10~12μm; and the average particle size D50 of the waste incineration fly ash is 12~17μm.

[0009] Preferably, the sodium silicate has a modulus of 1.6; and the quartz sand has a particle size of 70-120 mesh.

[0010] Preferably, the calcium silicate board has a thickness of 10-25 mm and a density of 1.0~1.5 g / cm³.

[0011] Preferably, the size of the calcium silicate board can be customized according to laboratory testing requirements.

[0012] A method for preparing laboratory-prepared waste incineration fly ash-based calcium silicate boards as described in any of the above claims, characterized by comprising the following steps: According to the formula, paper pulp fibers, sodium silicate and water are mixed and stirred to form fiber pulp; According to the proportions, cement, fly ash, silica fume, desulfurization gypsum, waste incineration fly ash, and quartz sand are mixed and stirred to form a powder. The fiber slurry and powder are mixed and stirred to form a pressed material; The pressed material is pressed and shaped under a press using a mold to form a slab; The slab is steam-cured in an autoclave to form a sheet material; The final calcium silicate board is obtained after the board is dried.

[0013] Preferably, the length of the pulp fiber is 3~6mm, and the tobermorite crystal phase inside the calcium silicate board can grow along the direction of the pulp fiber to form a ternary composite network structure of fiber-crystal phase-gel phase.

[0014] Preferably, the stirring speed of the fiber slurry is 140 r / min; the stirring speed of the powder is 140 r / min; and the stirring speed of the pressed material is 140~280 r / min.

[0015] Preferably, the pressure for the pressurization molding is 30~40MPa, and the pressurization time is 15~20min; the temperature for the autoclaving is 180℃, the pressure is 1.05MPa, and the curing time is 6~8h; the temperature for the drying is 105℃, and the drying time is 24~48h.

[0016] Preferably, during the mixing process, the powder is added to the fiber slurry in 3 to 5 batches, and after each batch is added, it is stirred for 5 to 8 minutes before the next batch is added.

[0017] The beneficial effects of this invention are: This invention provides a laboratory preparation method for calcium silicate boards based on waste incineration fly ash. By using waste incineration fly ash as the main calcium source, combined with various raw materials and a specific preparation process, it realizes the resource utilization of hazardous solid waste, reduces the consumption of natural mineral resources and the accumulation of hazardous waste, and lowers environmental risks. As the background technology shows, waste incineration fly ash is hazardous solid waste. Existing treatment methods cannot balance the output, and long-term accumulation and landfilling pose a risk of toxic substance leakage, easily causing chemical pollution incidents and irreversible environmental impacts. This invention optimizes the raw material composition, ensuring that solid waste accounts for 80% of the ash content, while the amount of waste incineration fly ash incorporated exceeds 50%. This significantly solves the problem of excessive accumulation of waste incineration fly ash that cannot be recycled. At the same time, it replaces natural raw materials in traditional production processes with solid waste, greatly reducing the consumption of natural resources and achieving both environmental and economic benefits. Furthermore, by optimizing the raw material ratio, especially by introducing specific amounts of pulp fiber and sodium silicate, the fiber guides the directional growth of hydrothermal synthesis products, forming a reinforced and toughened fiber-crystalline phase-gel phase ternary network structure, which greatly improves the comprehensive performance of the board. Meanwhile, the laboratory miniaturization preparation method can simulate the entire industrial production process, providing reliable pre-experimental data guidance for subsequent large-scale industrial production, achieving environmental, economic, and practical benefits. Attached Figure Description

[0018] Figure 1 This is a flowchart of a laboratory method for preparing calcium silicate board based on waste incineration fly ash according to the present invention.

[0019] Figure 2 This is a reference diagram showing the physical state of the present invention.

[0020] Figure 3 This is a schematic diagram of the ternary composite network structure of the fiber-crystalline phase-gel phase of the present invention.

[0021] It should be noted that these accompanying drawings and textual descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art by referring to specific embodiments. Detailed Implementation

[0022] Combination Figures 1-3 As shown, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0023] Example 1 This embodiment provides a laboratory preparation method for a waste incineration fly ash-based calcium silicate board. The raw material composition and preparation process are as follows: Step 1, Raw Material Preparation: Accurately weigh each raw material according to the mass percentage, specifically: 22 parts cement with an average particle size D50 of 14.5 micrometers; 13 parts fly ash with an average particle size D50 of 24 micrometers; 4 parts desulfurized gypsum with an average particle size D50 of 11 micrometers; 4 parts silica fume with an average particle size D50 of 9 micrometers; 65 parts waste incineration fly ash with an average particle size D50 of 15 micrometers; 90 parts quartz sand with a particle size of 100 mesh; 13 parts sodium silicate with a modulus of 1.6; 6.5 parts pulp fiber with a length of 4 mm; and 57 parts water.

[0024] The second step is to prepare the fiber pulp: add the weighed pulp fibers, sodium silicate and water into a mixing container, and mix at a stirring speed of 140 revolutions per minute for 15 minutes until the fibers are evenly dispersed to obtain the fiber pulp.

[0025] The third step is to prepare the powder: put cement, fly ash, silica fume, desulfurized gypsum, waste incineration fly ash and quartz sand into a dry powder mixer and dry mix them at a speed of 140 revolutions per minute for 20 minutes to obtain a uniformly mixed powder.

[0026] Step 4, preparing the pressing material: Divide the powder obtained in step 3 into four batches and slowly add them to the fiber slurry obtained in step 2. Control the mixing speed at 200 revolutions per minute. After each batch of powder is added, continue mixing for 7 minutes to ensure uniform mixing before adding the next batch, until all the powder is added and mixed into a uniform and viscous pressing material.

[0027] Step 5, pressure molding: Quickly fill the blank into a mold with dimensions of 300 mm x 300 mm x 12 mm, place it under a press, and press it into shape at a pressure of 35 MPa for 18 minutes. Then demold to obtain a dense wet slab.

[0028] Step 6, Autoclaving: Transfer the wet slab to an autoclave. After closing the autoclave door, introduce saturated steam and raise the temperature and pressure to 180 degrees Celsius and 1.05 MPa. Under these conditions, maintain constant temperature and pressure for 7 hours. The high-temperature, high-pressure hydrothermal reaction promotes the formation of tobermorite crystals and the solidification of heavy metals. After curing, allow the pressure and temperature to drop naturally to room temperature, and remove the slab to obtain the preliminary finished product.

[0029] Step 7, Drying: Place the autoclaved board in a forced-air drying oven and dry it at 105 degrees Celsius for 36 hours to remove excess moisture from the board, and finally obtain the laboratory waste incineration fly ash-based calcium silicate board.

[0030] The waste-to-lime silicate board prepared in this embodiment has a thickness of 18 mm, a density of 1.2 g / cm³, and dimensions that meet laboratory standard testing requirements. Testing revealed that the board contains 68% tobermorite by mass, forming a stable ternary composite network structure of fiber-crystalline phase-gel phase. According to TCLP standards, the heavy metal leaching concentrations were Cu 0.048 mg / L, Zn 0.582 mg / L, Pb 0.045 mg / L, Cr 0.012 mg / L, and Cd 0.018 mg / L, all far below national environmental protection limits. In terms of mechanical properties, the flexural strength is 7.95 MPa, the water absorption rate is 17.5%, and the thermal conductivity is 0.24 W / (mK). Its overall performance is superior to traditional calcium silicate boards and existing waste-to-lime silicate-based building materials.

[0031] Example 2 The main difference between this embodiment and Embodiment 1 lies in the raw material ratio and some process parameters, in order to illustrate the adjustability of the present invention.

[0032] The raw materials are prepared by weight as follows: 20 parts cement, with an average particle size D50 of 13 micrometers; 10 parts fly ash, with an average particle size D50 of 22 micrometers; 3 parts desulfurized gypsum, with an average particle size D50 of 10 micrometers; 3 parts silica fume, with an average particle size D50 of 8 micrometers; 50 parts waste incineration fly ash, with an average particle size D50 of 12 micrometers; 80 parts quartz sand, with a particle size of 70 mesh; 10 parts sodium silicate with a modulus of 1.6; 5 parts pulp fiber with a length of 3 mm; and 54 parts water.

[0033] According to the formula, pulp fiber, sodium silicate, and water are added to a mixer and stirred at 140 r / min for 12 min to form a uniformly dispersed fiber slurry. Cement, fly ash, silica fume, desulfurized gypsum, waste incineration fly ash, and quartz sand are mixed according to the formula and stirred at 140 r / min for 18 min to obtain a uniformly mixed powder. The powder is added to the fiber slurry in three batches, and after each batch is added, it is stirred at 140 r / min for 5 min. After all the materials are added, stirring is continued for 12 min to form a uniform pressing material. The pressing material is placed into a custom mold and pressed under a press at 30 MPa for 15 min. After demolding, a slab is obtained. The slab is placed in an autoclave and cured at 180℃ and 1.05 MPa for 6 h. The cured slab is placed in a drying oven and dried at 105℃ for 24 h to obtain the final product.

[0034] The calcium silicate board prepared in this embodiment has a thickness of 10 mm and a density of 1.3 g / cm³, and the size can be customized according to laboratory testing requirements. Testing revealed that the board contains 62% tobermorite by mass, and its ternary composite network structure is intact; the heavy metal leaching concentrations are Cu 0.063 mg / L, Zn 0.715 mg / L, Pb 0.068 mg / L, Cr 0.015 mg / L, and Cd 0.029 mg / L, meeting environmental protection requirements; the flexural strength is 10.3 MPa, the water absorption rate is 15.1%, and the thermal conductivity is 0.23 W / (mK), meeting the laboratory's basic performance testing standards for building materials.

[0035] Example 3 This embodiment provides a laboratory preparation method for a waste incineration fly ash-based calcium silicate board. The raw material composition and preparation process are as follows: The raw materials are prepared by weighing as follows by weight: 25 parts cement, with an average particle size D50 of 16 micrometers; 15 parts fly ash, with an average particle size D50 of 26 micrometers; 5 parts desulfurized gypsum, with an average particle size D50 of 12 micrometers; 5 parts silica fume, with an average particle size D50 of 10 micrometers; 80 parts waste incineration fly ash, with an average particle size D50 of 17 micrometers; 100 parts quartz sand, with a particle size of 120 mesh; 15 parts sodium silicate with a modulus of 1.6; 8 parts pulp fiber with a length of 6 mm; and 60 parts water.

[0036] According to the formula, add pulp fiber, sodium silicate and water to a mixer and stir at 140 r / min for 18 min to ensure uniform fiber dispersion; mix the powder raw materials according to the formula and stir at 140 r / min for 22 min to obtain uniform powder; add the powder to the fiber pulp in 5 batches, stirring at 280 r / min for 8 min after each batch is added, and continue stirring for 20 min after all the materials are added to form a high-quality pressing material; put the pressing material into a mold and press it at 40 MPa for 20 min to demold and obtain a slab; place the slab in an autoclave and cure it at 180℃ and 1.05 MPa for 8 h; place the slab in a drying oven and dry it at 105℃ for 48 h to obtain the final product.

[0037] The calcium silicate board prepared in this embodiment has a thickness of 25 mm and a density of 1.5 g / cm³, making it suitable for large-scale mechanical property testing equipment in the laboratory. Testing revealed that the board contains 72% tobermorite by mass, exhibiting a dense structure; the heavy metal leaching concentrations are Cu 0.039 mg / L, Zn 0.498 mg / L, Pb 0.037 mg / L, Cr 0.010 mg / L, and Cd 0.014 mg / L, demonstrating excellent curing performance; the flexural strength is 11.9 MPa, the water absorption rate is 20.1%, and the thermal conductivity is 0.18 W / (mK), exhibiting outstanding mechanical and thermal insulation properties.

[0038] Example 4 This embodiment provides a laboratory preparation method for a waste incineration fly ash-based calcium silicate board. The raw material composition and preparation process are as follows: The raw materials are prepared by weighing as follows by weight: 28 parts cement, with an average particle size D50 of 16 micrometers; 28 parts fly ash, with an average particle size D50 of 26 micrometers; 4 parts desulfurized gypsum, with an average particle size D50 of 12 micrometers; 8 parts silica fume, with an average particle size D50 of 10 micrometers; 70 parts waste incineration fly ash, with an average particle size D50 of 17 micrometers; 100 parts quartz sand, with a particle size of 120 mesh; 15 parts sodium silicate with a modulus of 1.6; 8 parts pulp fibers with a length of 6 mm; and 60 parts water.

[0039] According to the formula, add pulp fiber, sodium silicate and water to a mixer and stir at 140 r / min for 18 min to ensure uniform fiber dispersion; mix the powder raw materials according to the formula and stir at 140 r / min for 22 min to obtain uniform powder; add the powder to the fiber pulp in 5 batches, stirring at 280 r / min for 8 min after each batch is added, and continue stirring for 20 min after all the materials are added to form a high-quality pressing material; put the pressing material into a mold and press it at 40 MPa for 20 min to demold and obtain a slab; place the slab in an autoclave and cure it at 180℃ and 1.05 MPa for 8 h; place the slab in a drying oven and dry it at 105℃ for 48 h to obtain the final product.

[0040] The calcium silicate board prepared in this embodiment has a thickness of 10 mm and a density of 1.5 g / cm³, making it suitable for large-scale mechanical property testing equipment in the laboratory. Testing revealed that the board contains 72% tobermorite by mass, exhibiting a dense structure; the heavy metal leaching concentrations are Cu 0.01 mg / L, Zn 0.16 mg / L, Pb 0.001 mg / L, Cr 0.21 mg / L, and Cd 0.014 mg / L, demonstrating excellent curing performance; the flexural strength is 10.58 MPa, the water absorption rate is 19.9%, and the thermal conductivity is 0.18 W / (mK), exhibiting outstanding mechanical and thermal insulation properties.

[0041] Finally, it should be noted that the above description is merely a preferred embodiment of the present invention and is only used to illustrate the technical solution of the present invention, and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of protection of the present invention.

Claims

1. A laboratory-prepared waste incineration fly ash-based calcium silicate board, characterized in that, By weight, it includes: 20-25 parts cement, 10-15 parts fly ash, 3-5 parts desulfurized gypsum, 3-5 parts silica fume, 50-80 parts waste incineration fly ash, 80-100 parts quartz sand, 10-15 parts sodium silicate, 5-8 parts pulp fiber, and 54-60 parts water. The modulus of the sodium silicate is 1.

6. The particle size of the quartz sand is 70-120 mesh. The length of the pulp fiber is 3-6 mm. The tobermorite crystal phase inside the calcium silicate board can grow along the direction of the pulp fiber to form a ternary composite network structure of fiber-crystal phase-gel phase.

2. The waste incineration fly ash-based calcium silicate board prepared in the laboratory as described in claim 1, characterized in that: The average particle size D50 of the cement is 13~16μm; the average particle size D50 of the fly ash is 22~26μm; the average particle size D50 of the silica fume is 8~10μm; the average particle size D50 of the desulfurized gypsum is 10~12μm; and the average particle size D50 of the waste incineration fly ash is 12~17μm.

3. The laboratory-prepared waste incineration fly ash-based calcium silicate board as described in claim 1, characterized in that: The thickness of the calcium silicate board is 10-25 mm, and the density is 1.0~1.5 g / cm³.

4. The waste incineration fly ash-based calcium silicate board prepared in the laboratory as described in claim 3, characterized in that: The size of the calcium silicate board can be customized according to laboratory testing requirements.

5. A method for preparing a waste incineration fly ash-based calcium silicate board according to any one of claims 1-4, characterized in that, Includes the following steps: According to the formula, paper pulp fibers, sodium silicate and water are mixed and stirred to form fiber pulp; According to the proportions, cement, fly ash, silica fume, desulfurization gypsum, waste incineration fly ash, and quartz sand are mixed and stirred to form a powder. The fiber slurry and powder are mixed and stirred to form a pressed material; The pressed material is pressed and shaped under a press using a mold to form a slab; The slab is steam-cured in an autoclave to form a sheet material; The final calcium silicate board is obtained after the board is dried.

6. The method for preparing a laboratory-grown waste incineration fly ash-based calcium silicate board as described in claim 5, characterized in that: The stirring speed of the fiber slurry is 140 r / min; the stirring speed of the powder is 140 r / min; and the stirring speed of the pressed material is 140~280 r / min.

7. The method for preparing a laboratory-grown waste incineration fly ash-based calcium silicate board as described in claim 5, characterized in that: The pressure for the pressurization molding is 30~40MPa, and the pressurization time is 15~20min; the temperature for the autoclaving is 180℃, the pressure is 1.05MPa, and the curing time is 6~8h; the temperature for the drying is 105℃, and the drying time is 24~48h.

8. The method for preparing a laboratory-grown waste incineration fly ash-based calcium silicate board as described in claim 6, characterized in that: During the mixing process, the powder is added to the fiber slurry in 3 to 5 batches. After each batch is added, the mixture is stirred for 5 to 8 minutes before adding the next batch.

Citation Information

Patent Citations

  • Calcium silicate board prepared from solid waste and preparation method thereof

    CN115819060A

  • Cooperative treatment method and system for waste incineration fly ash and silicon-rich waste

    CN116283094A